2021
DOI: 10.1021/acs.inorgchem.1c01781
|View full text |Cite
|
Sign up to set email alerts
|

Co-Heteroatom-Based MOFs for Bifunctional Electrocatalysts for Oxygen and Hydrogen Evolution Reactions

Abstract: Herein, a Co­(II) heteroatom metal–organic framework was successfully post-modified via unsaturated coordinated S precisely capturing Ni2+ on the surface of the porous structure. The newly pristine bimetallic MOFs have increasing active edge sites (Ni­(II) and S), boosting electrocatalytic activity toward oxygen evolution reaction and hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, in addition to its excellent ORR activity, it also has exceptional performance in the HER and OER catalytic processes. [140][141][142] Xu et al [143] reported the embedding of a single cobalt atom in a sandwich-like multimodally porous N-doped dualcarbon architecture to achieve fast electron transfer, accelerated oxygen/electrolyte diffusion, and timely water removal by exploiting the abundant Co-N 4 active centers of the catalyst and the optimized multimodal pore structure with a half-wave potential of 0.72 V, comparable with commercial Pt/C. Aside from the single ORR catalytic activity, Doan et al [136] designed cobalt single atoms (CoSAs)-MoS 2 nanosheets grown vertically on 3D TiN nanorod arrays.…”
Section: Nonnoble Metal Single-atom Electrocatalystsmentioning
confidence: 99%
“…Furthermore, in addition to its excellent ORR activity, it also has exceptional performance in the HER and OER catalytic processes. [140][141][142] Xu et al [143] reported the embedding of a single cobalt atom in a sandwich-like multimodally porous N-doped dualcarbon architecture to achieve fast electron transfer, accelerated oxygen/electrolyte diffusion, and timely water removal by exploiting the abundant Co-N 4 active centers of the catalyst and the optimized multimodal pore structure with a half-wave potential of 0.72 V, comparable with commercial Pt/C. Aside from the single ORR catalytic activity, Doan et al [136] designed cobalt single atoms (CoSAs)-MoS 2 nanosheets grown vertically on 3D TiN nanorod arrays.…”
Section: Nonnoble Metal Single-atom Electrocatalystsmentioning
confidence: 99%